PENGARUH TARI MEDLEY NUSANTARA TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ISLAM MENTARI BUNDA PADANG - Maharani, Indra Yeni; Yulsyofriend, Setiyo Utoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to examine how the Nusantara Medley Dance affects the gross motor skills of the five to six-year-old students at Mentari Bunda Islamic Kindergarten in Padang. The gross motor skills of children are still developing. This is evident in morning workouts, where some kids struggle to stay balanced when standing on tiptoe and lifting one leg during warm-up exercises. They also struggle to support their body weight when bending their legs with their arms outstretched, and they have trouble shifting positions when switching to gymnastic moves. Additionally, teachers choose fewer activities to help kids develop their gross motor abilities. This study employs a quasi-experimental research design and a quantitative methodology. All of the students at Mentari Bunda Islamic Kindergarten in Padang made up the study's population. Class B1 served as the experimental class and class B2 as the control class; each class had 15 students. Normality, homogeneity, and hypothesis testing were employed in data analysis procedures. The sig column in Levene's test of variance is 0.939>0.05, according to the hypothesis test table. This figure shows that 0.000 is less than 0.05. If the sig value is less than 0.05, it is in compliance with the measurement criteria of the hypothesis test. Thus, it can be said that Ho is rejected while Ha is accepted. According to the study's findings, children between the ages of five and six benefit from using Indonesian medley dance in terms of their gross motor abilities.